Influence of filling sequence of concrete faced rockfill dam on deformation of squeezed sidewall and dam - Hongru, Li; Min, Yang; Jiaqi, Li (Frontiers in Earth Science, 2023)
During construction of concrete faced rockfill dam (CFRD), the extrusion-sidewall will be protruding or deficiency under normal. Before panel construction, local slope cutting should be taken for the squeezed side wall or supplementary filling measures should be taken after excavating the squeezed side wall, which will affect the mechanical deformation of the panel. According to the monitoring data of concrete-faced rockfill dams of some hydro-electric station in Hubei Province, the three-dimensional finite element analysis method is used to simulate the original filling sequence process of the concrete face rockfill dam. By comparing the difference between the monitoring data and the calculation results, the deformation law of the extrusion side wall and the dam is obtained, which verifies the rationality of the three-dimensional simulation analysis of the dam. The characteristic values of settlement and horizontal displacement obtained from dam monitoring and numerical calculation are compared with those of other high concrete faced rockfill dams. The characteristic values of this dam are close to those of general concrete faced rockfill dams. The deformation law of extrusion side wall and dam under two optimization schemes with different filling sequence is studied. It is found that if conditions permit, the upstream should be filled first and then the downstream to reduce the deformation of extrusion side wall to the upstream.